Pengaruh Bauran Pemasaran 7P Terhadap Keputusan Pembelian Pada Aplikasi Netflix - Aditya Rian Ramadhan (Journal of Trends Economics and Accounting Research, 2024)
This study aims to analyze the influence of the 7P Marketing Mix on social media on purchase decisions for the Netflix application. The analysis method used in this research is quantitative data. The testing stages carried out in this study include validity tests, reliability tests, classical assumption tests, multiple linear regression, partial tests (T-test), simultaneous tests (F-test), and the coefficient of determination (R²). Data collection in this study was conducted using a questionnaire instrument with a sample size of 96 respondents, specifically from the Bekasi community who have subscribed to the Netflix application. The sampling method used in this research is purposive sampling with the assistance of IBM SPSS statistics 25 software. The results of the T-test showed that the calculated T-value is smaller than the critical T-value for the following variables: Product (0.003 < 1.985), Promotion (0.663 > 1.985), Place (1.673 > 1.985), People (0.890 > 1.985), Process (1.576 > 1.985), and Physical Evidence (0.676 > 1.985), indicating that these six variables do not have a partial effect on the purchase decision for Netflix subscriptions. However, Price has a calculated T-value greater than the critical T-value (4.588 > 1.985), indicating that the price variable partially influences the purchase decision for Netflix subscriptions. The results of the F-test show that Product, Price, Promotion, Place, People, Process, and Physical Evidence simultaneously influence the purchase decision for the Netflix application.